A green, efficient alternative to fracking that can prevent earthquakes. (Research'eu results magazine)
Whilst the extraction of shale gas in a safe and responsible way is an EU priority, an extraction method easing public concerns has yet to found. Hydraulic fracturing-commonly known as 'frackling'-not only fails to fit the bill, it is also known to trigger earthquakes. A UK-based company is putting forward a promising alternative in the EU-funded OCTOPUS TECHNOLOGY project.